Sempervirine Inhibits Proliferation and Promotes Apoptosis by Regulating Wnt/β-Catenin Pathway in Human Hepatocellular Carcinoma - Yue, Rongcai; Liu, Haiping; Huang, Yaxin; Wang, Jing; Shi, Dongmei; Su, Yanping; Luo, Yufei; Cai, Ping; Jin, Guilin; Yu, Changxi (Frontiers in Pharmacology, 2021)
Gelsemium elegans (G. elegans) Benth., recognized as a toxic plant, has been used as traditional Chinese medicine for the treatment of neuropathic pain and cancer for many years. In the present study, we aim to obtain the anti-tumor effects of alkaloids of G. elegans and their active components in hepatocellular carcinoma (HCC) and the potential mechanism was also further investigated. We demonstrated that sempervirine induced HCC cells apoptosis and the apoptosis was associated with cell cycle arrest during the G1 phase, up-regulation of p53 and down-regulation of cyclin D1, cyclin B1 and CDK2. Furthermore, sempervirine inhibited HCC tumor growth and enhances the anti-tumor effect of sorafenib in vivo. In addition, inactivation of Wnt/β-catenin pathway was found to be involved in sempervirine-induced HCC proliferation. The present study demonstrated that alkaloids of G. elegans were a valuable source of active compounds with anti-tumor activity. Our findings justified that the active compound sempervirine inhibited proliferation and induced apoptosis in HCC by regulating Wnt/β-catenin pathway.